If high aircraft noise exposure increases heart attack risks, what do we do about it? - Brooker, Peter (Institute of Acoustics, 2006)
Is high aircraft noise exposure actually dangerous to people’s health? Is there a good way of identifying ‘significant danger’? What are the policy implications for government and airport operators of people being exposed to significant danger? One of the most difficult questions faced by medical researchers is often that of judging whether an exposure to some potential hazard causes a disease or some other kind of impairment or ill health. There is a huge literature on ‘Epidemiology’ – the scientific study of factors affecting the illnesses and health of individuals and populations.